Dom Pedro Paulo Koop: Notas biográficas, atuação no Concílio e aspectos da recepção do Vaticano II na Diocese de Lins – São Paulo - Ferreira, Reuberson Rodrigues (Revista Eclesiástica Brasileira, 2024)
O presente artigo tem por objetivo analisar a figura do bispo de Lins no período imediatamente anterior à celebração do Concílio Ecumênico Vaticano II, sua atuação no interior do Concílio e a recepção deste na referida diocese. O texto molda-se por três partes. Na primeira revelam-se traços biográficos do Bispo. Na segunda aponta-se sua atuação no Concílio, e, na terceira, como a figura do prelado, à luz da teologia da recepção, desenhou linhas para uma imediata recepção do Concílio, em Lins. Abstract: The present article has the objective of analyze the bishop of Lins in the period immediately before the celebration of the Second Vatican Ecumenical Council, his work in the Council, and the subsequent reception that was given to him in that diocese. The text is molded in three parts. The first part reveals the Bishop’s biographical traits. In the second, his participation in the Council is pointed out, and in the third, how the figure of the prelate, in the light of the theology of reception, drew lines for an immediate reception of the Council in Lins. Keywords: Dom Pedro Paulo Koop; Vatican II; Bishop; Reception.